(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
It was thought about teaching elementary school students to write correctly without spelling mistakes and teaching the spelling of capital letters to elementary school students from the 1st grade.